Découverte d’une tuile estampillée de la fin du ier s. av. J.-C. à Bibracte (mont Beuvray, Saône-et-Loire) - Florent Delencre; Quentin Verriez; Chiara Martini-Picot (Gallia)
In 2018 the discovery of the first stamped tile in domus PC2 in the oppidum of Bibracte is attributed to the thorough application of a sorting and inventory protocol, established very early on, regarding Roman building materials made of terracotta. This mark, thought to be S. AV or S. AN, is stamped on a fragment of a tegula, which was apparently produced locally at the latest by the end of the 1st c. BC and in a place located close to Mount Beuvray. It was discovered in the specific context of the remodelling of a domus, a typical example of luxurious Italian-style houses that flourished in Bibracte after Caesar’s conquest. This stamped tile bears the most ancient mark found on a building material on the Aeduan territory and testifies of the incorporation of Roman practices at a decisive moment in the history of Gaul. Indeed, this stamp raises the question of the subsequent diffusion of this norm throughout Gaul and it can be compared to contemporary productions in the Italian peninsula. These initials make it possible to identify the owner of the workshop that produced this tile. It can be assumed that this craftsman had acquired Roman citizenship and that he played a prominent role in the spread of new architectural norms from Italy used for the buildings of Bibracte. These were incorporated at a very early point in time, during the mid-1st c. BC. Such elements, closely related to the incorporation of new Italian-style architectural norms into the constructions of the oppidum of Bibracte, can be considered as indicating a rapid and early romanisation process of the Aeduan elites, close to the Roman world. This stamped tile can thus be considered as a cultural marker clearly revealing the deep transformations of the Aeduan territory following the Gallic wars.